Hubungan Harga Diri Remaja dengan Penyalahgunaan Alkohol - Asriyani M. Arifin (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the relationship between adolescent self-esteem and alcohol abuse. The theoretical model used is planned behavior which explains that the determinant of health-related behavior such as consuming alcohol is the intensity or desire of a person to do this behavior. This research was conducted in high schools in the city of Tidore Kepulauan with the category of adolescence 13-16 years. Using a quantitative approach with a survey method, the study sample was 200 respondents. Data analysis used SPSS version 22. Based on the results of the analysis, the correlation coefficient was -0.773 and the determination coefficient was 60%. The conclusion of this study is that self-esteem has a relationship with a tendency to abuse alcohol. The negative correlation coefficient indicates that there is a negative relationship direction, namely the lower the level of self-esteem, the higher the level of tendency to abuse alcohol, and vice versa. The coefficient of determining self-esteem with a tendency to abuse alcohol is 60%, while the remaining 40% is influenced by factors other than self-esteem such as external factors.